Intracellular label-free detection of mesenchymal stem cell metabolism within a perivascular niche-on-a-chip. Issue 7 (19th February 2021) - Perottoni, Simone; Neto, Nuno G. B.; Di Nitto, Cesare; Dmitriev, Ruslan I.; Raimondi, Manuela Teresa; Monaghan, Michael G.
Abstract : The stem cell niche at the perivascular space plays a role in dictating the fate of stem cells within it. This study predicts in silico and models the perivascular space, in a miniaturised bioreactor, with non-invasive assessment of cell metabolism. Abstract : The stem cell niche at the perivascular space in human tissue plays a pivotal role in dictating the overall fate of stem cells within it. Mesenchymal stem cells (MSCs) in particular, experience influential microenvironmental conditions, which induce specific metabolic profiles that affect processes of cell differentiation and dysregulation of the immunomodulatory function. Reports focusing specifically on the metabolic status of MSCs under the effect of pathophysiological stimuli – in terms of flow velocities, shear stresses or oxygen tension – do not model heterogeneous gradients, highlighting the need for more advanced models reproducing the metabolic niche. Organ-on-a-chip technology offers the most advanced tools for stem cell niche modelling thus allowing for controlled dynamic culture conditions while profiling tuneable oxygen tension gradients. However, current systems for live cell detection of metabolic activity inside microfluidic devices require the integration of microsensors. The presence of such microsensors poses the potential to alter microfluidics and their resolution does not enable intracellular measurements but rather a global representation concerning cellular metabolism. Here, we present a metabolic toolbox coupling a miniaturised in vitro system for human-MSCs dynamic culture, which mimics microenvironmental conditions of the perivascular niche, with high-resolution imaging of cell metabolism. Using fluorescence lifetime imaging microscopy (FLIM) we monitor the spatial metabolic machinery and correlate it with experimentally validated intracellular oxygen concentration after designing the oxygen tension decay along the fluidic chamber by in silico models prediction. Our platform allows the metabolic regulation of MSCs, mimicking the physiological niche in space and time, and its real-time monitoring representing a functional tool for modelling perivascular niches, relevant diseases and metabolic-related uptake of pharmaceuticals.